FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN USAHA DAGANG PELINGGIH DI KECAMATAN MENGWI - Dewi, Ni Made Ayu Aprinia; Wenagama, I Wayan (Buletin Studi Ekonomi; VOL.24.NO.2.AGUSTUS 2019, 2019)
Abstract: Factors that Influence Pelinggih Trade Revenue in Mengwi District. Hindus in Bali have a tradition and the thickness of typical rituals such as giving banten. Mengwi Subdistrict as an industrial center has pelinggih trading business as a source of income for the community. This study aims to determine the effect of capital, labor, raw materials and duration of business simultaneously and partially on the income of the trading business in Mengwi District. The data used in this study are primary data, namely by distributing questionnaires to the traders in Mengwi Subdistrict. The population used in this study was all traders in Mengwi Subdistrict. The number of samples used were many as 57 traders, using proportional random sampling sampling techniques. The variables studied in this study are capital, labor, raw materials, length of business and income of pelinggih traders. The analysis technique used in this study is Multiple Linear Regression. Based on the results of the study it was stated that capital, labor, raw materials and duration of business simultaneously had a significant effect on the income of pelinggih trading businesses in Mengwi District. Partially, capital, labor, raw materials and duration of business have a positive and significant effect on the income of the pelinggih trading business in Mengwi District. Keywords: Income; capital; labor; raw materials; length of business.